Effect of different treatment on Surface Morphology of laser bleached teeth: SEM Evaluation - Mohammadi Basir, Mahshid; Rezvani, Mohammad Bagher; Chiniforush, Nasim; Moradi, Zohreh (Journal of Dental School, 2020)
Objective: The aim of this study was to evaluate and compare the effect of dental surface treatment with Er:YAG , Nd:YAG ,CO2 lasers and sodium ascorbate to recently laser bleached enamel by scanning electron microscope (SEM). Methods: 15caries-free extracted human third molars were selected for this study. The samples were bleached by Heydent JW power activated by diode laser 810 nm. After 7 day, the bleaching procedure was repeated as same as first time. Then, the samples were divided to five groups randomly as follow: Group 1: treated using Nd:YAG laser with output power of 1 W, Group 2: treated using Er:YAG laser with output power of 0.5 W, Group 3: treated using CO2 laser with output power of 0.5 W, Group 4: sodium ascorbate 10%, Group 5: no surface treatment. After treatments, the surfaces were evaluated using Scanning Electron Microscope (SEM) analysis. Results: The surfaces treated by Nd:YAG laser showed some melting area but the surface treated by Er:YAG laser showed irregular and micro porous surface. CO2 laser treatment of surfaces resulted in melting of superficial layer of dental substrate and micro cracks. Sodium ascorbate did not change the surface except changes raised from bleaching. Conclusion: Laser conditioning of laser-bleached teeth can be beneficial for enhancing bond strength of resin material to recently bleached enamel.